Socio-Economic Factors Determining Tourism in Sheik Baddin National Park DI Khan Khyber PakhtunKhwa - MUHAMMAD LUQMAN; DR. MUHAMMAD AZAM KHAN; MUHAMMAD ARIF (Journal of Business & Tourism, 2021)
Tourism is one of the fastest growing industries which play a vital role in the prosperity and development of a country. The aim of present study is to investigate the socioeconomic factors determining tourists inflowsto Sheik Baddin National Park (SBNP), D.I Khan, Khyber Pakhtunkwa (KP). For this purpose, data has been collected through questionnaire and interview schedule from tourists in the surrounding of SBNP. For the analysis of the data the methods of descriptive statistics including regression, correlation, tabulation, and charts are used. The results reveals that the highest percentage of tourist’s age ranges from 10-30 year, where most of the young people about 80% visit park for recreation activities. The results reveals that there is strong correlation relationship in transportation and education, family monthly income and education, family monthly income and means of transportation, family monthly income and selection of national park, current employment status of visitor and education, and current employment status of visitor and family monthly income.